Heteroleptic (S^C)-cyclometallated gold(III) complexes as novel antiviral agents - María Balsera-Manzanero; Raquel G. Soengas; Marta Carretero-Ledesma; Carlos Ratia; M. José Iglesias; Jerónimo Pachón; Fernando López-Ortiz; Elisa Cordero; Sara M. Soto; Javier Sánchez-Céspedes (Heliyon, 2024)
Despite the increasingly widespread clinical impact of adenovirus (HAdV) infections in healthy individuals and the associated high morbidity in immunosuppressed patients, particularly among the paediatric population, a specific treatment for this virus has yet to be developed. In this study, we report the anti-HAdV activity of sub-micromolar concentrations of four heteroleptic (C^S)-cycloaurated complexes bearing a single thiophosphinamide [Au(dpta)Cl2, Au(dpta)(mrdtc), and Au(dpta)(dedtc)] or thiophosphonamide [Au(bpta)(dedtc)] chelating ligand and a dithiocarbamate moiety. In addition to their low cytotoxicity, the findings of mechanistic assays revealed that these molecules have antiviral activity by targeting stages of the viral replication cycle subsequent to DNA replication. Additionally, all four compounds showed a significant inhibition of human cytomegalovirus (HCMV) DNA replication, thereby providing evidence for potential broad-spectrum antiviral activity.